The method of bolt axial force looseness monitoring and control by piezoelectric ceramics in bolted joint structures. (April 2022) - Sun, Xinyao; Shao, Jinggan; Zhou, Yang; Yuan, Ci; Li, Yang; Li, Dalei
Aiming at the problem of bolt looseness in structures, this paper proposes an active control method of axial force monitoring through guided wave and axial force compensation via the inverse piezoelectric effect of a piezoelectric ceramic gasket. Based on the finite element model, the propagation process of guided wave wave in bolted connectors is analyzed, which shows that the transmitted wave energy increases with the increase of bolt clamping force. The analysis of the stress-strain characteristics of the axially polarized and radially polarized piezoelectric ceramic gasket shows that the axially polarized piezoelectric ceramic gasket is more suitable for the control of bolt clamping force. The finite element analysis of the application of piezoelectric ceramic gasket in bolt axial force control shows that the power of guided wave signal increases monotonously with the increase of loaded electric field strength. In accordance with these theoretical methods and research, an active control system for bolt axial force is established in this experiment. The system monitors the power of the guided wave signal in real time and controls the axial force of the bolt by adjusting the intensity of the piezoelectric effect, which achieves an accurate control effect.